DOSAGE TEST OF RHIZOBIUM AND MULTI-ORGANIC KOHEN FERTILIZER ON GROWTH AND PRODUCTION SOYBEAN (Glycine max L) - Sulardi, Sulardi; Hakim, Tharmizi; Wasito, Muhammad (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
The study aimed to determine the dose of Rhizobium and Kohen multi-organic fertilizer on the Growth and Production of Soybean (Glycine max L). The research method used a factorial Randomized Block Design (RBD) consisting of 2 factors with 16 treatment combinations and 2 blocks. which is the first factor in the administration of rhizobium (R) doses consisting of 4 levels, namely R0 = No Treatment, R1 = 5 g/kg seeds, R2 = 10 g/kg seeds, and R3 = 15 g/kg seeds. The second factor was the multi-organic kohen (S) fertilizer treatment consisting of 4 levels, namely S0 = No Treatment, S1 = 0.5 kg/plot, S2 = 1,5 kg/plot, and S3 = 2,5 kg/plot. The research parameters were plant height, number of productive branches, number of pods per sample, dry weight of seeds per plot, and dry weight of grain per sample.The results showed that treatment with rhizobium dose affected the parameters of dry weight of seeds per plot, but did not affect the parameters of plant height, number of productive branches, number of filled pods, dry weight of seeds per sample.The multiorganic kohen fertilizer treatment had an effect on the dry weight of seeds per plot, and dry weight of seeds per sample, but had no effect on the parameters of plant height, number of productive branches.The interaction of the dose of rhizobium and multi-organic kohen fertilizer did not affect all the observed parameters.